(untitled) (Avocetta, 2016)
The Black Woodpecker has a wide northern Palearctic range, but in much of western Europe it has a highly fragmented distribution. As these isolated populations are vulnerable to land cover change, a better understanding of the factors driving their presence is needed in the perspective of conservation. To shed light on the habitat preferences of the Black Woodpecker in the southern part of its range, we carried out a research in a large protected area, the Cilento and Vallo di Diano National Park (the first investigation on this species anywhere in southern Italy). We used a playback technique to detect occurrence of Black Woodpeckers, as well as sympatric woodpecker species, and recorded environmental characteristics that might explain the bird’s occurrence, such as tree species and stand age. The “extent of occurrence” of the Black Woodpecker was calculated, and its habitat preferences investigated. Occurrence of the species was clearly dependent on beech dominance, in contrast with the other woodpecker species, with an estimated total population for National Park 18.56 (± 6.19) pairs in beech-dominated woods. Habitat preferences were narrower compared to northern European populations, highlighting the dependence of this species on beech forests in southern Europe. Since beech forests in the Mediterranean region are predicted to recede due to climate change, our findings highlight the vulnerability of southern Black Woodpecker populations.